Examining relative age effects in fundamental skill proficiency in British children aged 6-11 years - Birch, S.; Cummings, L.; Oxford, S. W.; Duncan, M. J. (The Journal of Strength and Conditioning Research, 2016)
The relative age effect (RAE) suggests that there is a clustering of birth dates just after the cutoff used for sports selection in age-grouped sports and that in such circumstances, relatively older sportspeople may enjoy maturational and physical advantages over their younger peers. Few studies have examined this issue in nonselective groups of children, and none have examined whether there is evidence of any RAE in skill performance. The aim of this study was to assess whether there were differences in fundamental movement skill (FMS) proficiency within children placed in age groups according to the school year. Six FMS (sprint, side gallop, balance, jump, catch, and throw) were assessed in 539 school children (258 boys and 281 girls) aged 6-11 years (mean age ± SD = 7.7 ± 1.7 years). We examined differences in these FMS between gender groups and children born in different quarters of the year after controlling for age and body mass index (BMI). For balance, chronological age was significant as a covariate (p = 0.0001) with increases in age associated with increases in balance. Boys had significantly higher sprint mastery compared with girls (p = 0.012), and increased BMI was associated with poorer sprint mastery (p = 0.001). Boys had higher catching mastery than girls (p = 0.003), and children born in Q1 had significantly greater catching mastery than those born in Q2 (p = 0.015), Q3 (p = 0.019), and Q4 (p = 0.01). Results for throwing mastery also indicated higher mastery in boys compared with girls (p = 0.013) and that children born in Q1 had higher throwing proficiency than those born in Q4 (p = 0.038). These results are important if coaches are basing sport selection on measures of skilled performance, particularly in object-control skills. Categorizing children's skilled performance based on rounded down values of whole-year age may disadvantage children born relatively later in the selection year, whereas children born earlier in the selection year will likely evidence greater skill mastery and subsequent advantage for selection purposes.